Innovation of Teaching Tools during Robot Programming Learning to Promote Middle School Students’ Critical Thinking - Liu, Hehai; Sheng, Jie; Zhao, Li (Sustainability, 2022)
In the digital age, robotics education has gained much attention for cultivating learners’ design thinking, creative thinking, critical thinking, and cooperative abilities. In particular, critical thinking as one of the key competencies in Education for Sustainable Development (ESD) can stimulate imagination and creation. It is of great value to explore critical thinking cultivation in robot programming learning. Therefore, this study applied different teaching tools to take the content of “making a manipulator through programming and construction” in a robotics course as an experimental context to examine the promotion of learners’ critical thinking. Before the experiment, a pre-test was conducted to measure students’ critical thinking ability. Then, all students were divided randomly into two groups: one as an experimental group with the teaching tool of Construction–Criticism–Migration (CCM) instructional design, and the other as a control group with the traditional teaching tool of demonstrate–practice instructional design. After a 6-week experiment, the measurement of critical thinking was applied as a post-test. SPSS was used to conduct an independent sample t test and one-way ANOVA to explore whether students’ critical thinking ability had improved and whether differences were found between the experimental group and the control group after the 6-week experiment. The results showed that the experimental group students’ critical thinking ability significantly improved, whereas no significant difference was found before and after the experiment for the control group. A significant difference existed between the two groups. This study provides an example of a new instructional design teaching tool for the teaching of robot programming and can provide valuable suggestions for instructors in middle schools.